Introducing pre-schoolers and first graders to English: Pre-service teachers’ insights - Kaminski, Annett (Neofilolog, 2025)
This study focuses on the teaching of English as a foreign language to very young learners aged between five and seven years. In particular, it investigates which aspects pre-service teachers identify as challenging before and after their classroom experience as part of their teaching-based master’s dissertation. Applying thematic analysis, three different types of data for three pre-service teachers are examined: Firstly, their brainstorming notes written down before they started teaching, secondly their reflections on their teaching as expressed in their master’s dissertation and thirdly their thoughts as articulated in follow-up interviews. Findings of this small-scale study suggest that reflection on extended classroom practice can help pre-service teachers to gain a better understanding of their learners’ specific needs and to adapt their lessons accordingly.